Fireproof biomass molded floor and production process thereof

By using multi-layer structure and flame retardant reinforcement in biomass molded floors, the problem that biomass molded floors cannot be fire-proof is solved, and its flame retardant performance and safety are significantly improved.

CN119466259AActive Publication Date: 2025-02-18JIANGSU LONGINES NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411617567.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-24
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

At this stage, the addition of wood fibers during the preparation of biomass molded floors has caused fire resistance, which hinders the development of biomass molded floors.

Method used

The structure of the silent foam layer, the base layer, the medium layer, the printed film layer, the wear-resistant layer and the UV coating layer is arranged in sequence from bottom to top. The base layer contains a flame retardant reinforcement, and through a specific production process and material combination, Improve the flame retardant performance of the floor.

Benefits of technology

It significantly improves the flame retardant effect of biomass molded floors, solves the problem that the original floor cannot be fire-proof, and enhances the safety of the floor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132643690000131
    Figure BDA0005132643690000131
Patent Text Reader

Abstract

The invention discloses a fireproof biomass mould pressing floor and a production process thereof. The fireproof biomass mould pressing floor comprises a mute foam layer, a base layer, a middle material layer, a printing film layer, a wear-resistant layer and a UV lamination layer which are sequentially arranged from bottom to top. When the floor is burnt, double hydroxides on the heated flame-retardant reinforcer of the base layer are heated and decomposed to generate water vapor for diluting oxygen and combustible gas, and meanwhile, the double hydroxides and the zinc organic framework can generate oxides of zinc, magnesium and aluminum, and the oxides are matched with phosphate generated by burning organic phosphorus in the organic framework to form a compact carbon layer; the organic silicon structure can generate stable S -O and S -C structures and is compounded with boron to further reinforce the isolation effect of the carbon layer, ammonia gas and nitrogen dioxide gas are generated to further dilute oxygen and combustible gas, and the UV lamination layer can form a compact carbonization layer on the surface of the floor during combustion, so that the surface of the floor is protected; and the flame retardant reinforcer in the base layer is matched for use, and flame retardance is performed inside and outside the template, so that the flame retardant efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant board preparation, and in particular to a fireproof biomass molded floor and a production process thereof. Background Art

[0002] Floor decoration materials are an important element in the building decoration industry. Different types of floor decoration materials have different performances, which can greatly affect the comfort, aesthetics and safety of interior design. With the improvement of people's living standards and the rapid development of social production technology, the variety of floor decoration materials has continued to increase and their functions have continued to increase. People have also continuously put forward higher requirements for the practicality, decorativeness and environmental protection of floor decoration materials. Biomass molded floor is a commonly used floor decoration material, but because wood fiber needs to be added during its preparation process, the floor cannot be fireproof, which hinders the development of biomass molded floor. Summary of the invention

[0003] The purpose of the present invention is to provide a fire-proof biomass molded floor and its production process, which solves the problem that the current biomass molded floor has poor flame retardant effect.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A fireproof biomass molded floor, comprising a sound-proof foam layer, a base layer, a middle material layer, a printed film layer, a wear-resistant layer and a UV coating layer arranged in sequence from bottom to top;

[0006] The mute foam layer and the base layer are provided with lock buckles for splicing the floors, and the mute foam layer and the base layer are coated with adhesive;

[0007] The base layer comprises the following raw materials in parts by weight: 90-100 parts of PVC resin powder type 5, 90-100 parts of PVC resin powder type 7, 50-60 parts of wood fiber, 200-220 parts of calcium carbonate, 100-150 parts of recycled materials, 10-15 parts of flame retardant enhancer, 10-15 parts of stabilizer, 20-25 parts of foaming regulator, 1-3 parts of internal lubricant, 1-3 parts of external lubricant, 0.5-1 parts of white foaming agent, 0.5-1 parts of yellow foaming agent, 3-5 parts of 2-hydroxyethyl acrylate and 1-1.5 parts of oxidized wax;

[0008] The middle material layer is made of the following raw materials in parts by weight: 100-120 parts of PVC resin powder type 5, 400-500 parts of calcium carbonate, 35-45 parts of dioctyl terephthalate and 3-5 parts of stabilizer;

[0009] The stabilizer is the same as the stabilizer for the base layer;

[0010] The wear-resistant layer is made of surface paper with aluminum oxide added and impregnated with melamine resin;

[0011] The UV coating layer is made of the following raw materials in parts by weight: 20-30 parts of a modifier, 40-50 parts of methyl methacrylate, 10-15 parts of butyl methacrylate, 5-8 parts of a photoinitiator, 0.3-0.5 parts of a leveling agent and 20-30 parts of toluene.

[0012] The flame retardant reinforcing agent is prepared by the following steps:

[0013] Step A1: 4-formylphenylboronic acid, 2-aminobenzimidazole and ethanol are mixed evenly, reacted at a speed of 120-150 r / min and a temperature of 75-78° C. for 20-25 hours, then cooled to 20-25 hours, DOPO is added, and the reaction is continued for 10-15 hours to obtain intermediate 1;

[0014] Step A2: Trimethylolpropane monoallyl ether, intermediate 1 and toluene are mixed uniformly, nitrogen is introduced for protection, and reflux reaction is carried out for 3-5 hours at a speed of 60-80 r / min and a temperature of 115-120° C. to obtain intermediate 2; intermediate 2, tetramethyltetrahydrocyclotetrasiloxane and DMF are mixed uniformly, and chloroplatinic acid is added at a speed of 150-200 r / min and a temperature of 50-60° C. to react for 10-15 hours to obtain intermediate 3;

[0015] Step A3: The intermediate 3, zinc nitrate hexahydrate and DMF are mixed, stirred for 1-1.5 hours at a speed of 300-500 r / min and a temperature of 25-30° C., aged for 20-25 hours, filtered to remove the filtrate, dispersed the substrate in deionized water, added with magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride, reacted for 10-15 hours at a speed of 120-150 r / min and a temperature of 110-115° C., filtered and washed to neutrality to obtain a flame retardant enhancer.

[0016] The molar ratio of 4-formylphenylboronic acid, 2-aminobenzimidazole and DOPO in step A1 is 1:1:1.

[0017] The amount ratio of trimethylolpropane monoallyl ether and intermediate 1 described in step A2 is 1:1, the molar ratio of intermediate 2 and tetramethyltetrahydrocyclotetrasiloxane is 4:1, and the amount of chloroplatinic acid used is 1‰ of the mass of tetramethyltetrahydrocyclotetrasiloxane.

[0018] The molar ratio of the intermediate 3, zinc nitrate hexahydrate, magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride described in step A3 is 6:18:15:5:60:20.

[0019] The modifier is prepared by the following steps:

[0020] Step B1: hydroxyethyl methacrylate, aluminum chloride and DMF are mixed uniformly, and epichlorohydrin is added under stirring at a speed of 120-150 r / min and a temperature of 80-85° C., and the mixture is reacted for 1-1.5 hours, and then sodium hydroxide solution is added, and the reaction is continued for 2-3 hours to obtain intermediate 4;

[0021] Step B2: The intermediate 4, 1,3-bis(aminopropyl)tetramethyldisiloxane and DMF are mixed evenly, and the mixture is reacted for 6-8 hours at a rotation speed of 150-200 r / min, a temperature of 30-40°C and a pH value of 9-10 to obtain the intermediate 5. The intermediate 5, triethylamine and DMF are mixed evenly, and diphenyl chlorophosphate is added at a rotation speed of 60-80 r / min and a temperature of 60-65°C to react for 20-25 hours to obtain the modifier.

[0022] The hydroxyethyl methacrylate, aluminum chloride, epichlorohydrin and sodium hydroxide solution described in step B1 are 1 mol:8.5 mmol:1 mol:160 mL, and the mass fraction of the sodium hydroxide solution is 35%.

[0023] The molar ratio of intermediate 4 and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B2 is 4:1, and the molar ratio of intermediate 5, triethylamine and diphenyl chlorophosphate is 1:4:4.

[0024] The production process of the fireproof biomass molded floor specifically includes the following steps:

[0025] The wear-resistant layer, printed film layer, middle material layer and base layer are overlapped and molded in sequence from top to bottom, lock buckles are installed between the base layer and the silent foam layer and adhesive is applied to bond them, a UV coating layer is coated on the surface of the wear-resistant layer and ultraviolet curing is performed to obtain a fire-resistant biomass molded floor.

[0026] Beneficial effects of the present invention: a fireproof biomass molded floor prepared by the present invention comprises a mute foam layer, a base layer, a middle material layer, a printed film layer, a wear-resistant layer and a UV coating layer arranged in sequence from bottom to top, the base layer comprises the following raw materials: PVC resin powder type 5, PVC resin powder type 7, wood fiber, calcium carbonate, recycled material, flame retardant enhancer, stabilizer, foaming regulator, internal lubricant, external lubricant, white foaming agent, yellow foaming agent, 2-hydroxyethyl acrylate and oxidized wax, the UV coating layer comprises the following raw materials: modifier, methyl methacrylate, butyl methacrylate, photoinitiator, leveling agent and toluene, flame retardant The enhancer uses 4-formylphenylboronic acid and 2-aminobenzimidazole as raw materials, so that the aldehyde group on the 4-formylphenylboronic acid reacts with the amino group on the 2-aminobenzimidazole to form an N=C bond, and then reacts with DOPO, so that the N=C bond reacts with the PH bond on DOPO to obtain an intermediate 1, trimethylolpropane monoallyl ether reacts with the intermediate 1, so that the hydroxyl group on the trimethylolpropane monoallyl ether reacts with the boric acid group on the intermediate 1 to obtain an intermediate 2, and the intermediate 2 reacts with tetramethyltetrahydrocyclotetrasiloxane under the action of chloroplatinic acid, so that the double bond on the intermediate 2 reacts with the S on the tetramethyltetrahydrocyclotetrasiloxane. iH bond reaction to obtain intermediate 3, intermediate 3 is reacted with zinc nitrate hexahydrate, so that the imidazole group on intermediate 3 and zinc ion cooperate to form a metal organic framework structure, and then magnesium chloride hexahydrate and aluminum chloride nonahydrate are added to form a double hydroxide load on the surface of the metal organic framework to obtain a flame retardant reinforcing agent. When the floor is burned, the double hydroxide on the flame retardant reinforcing agent is heated and decomposes to produce water vapor to dilute oxygen and combustible gas, and at the same time, it can react with the zinc organic framework to produce zinc, magnesium and aluminum oxides, and cooperate with the phosphate produced by the combustion of organic phosphorus in the organic framework to form a dense carbon layer, and the organic silicon structure can produce a stable S iO and Si-C structure, compounded with boron to further strengthen the insulation effect of the carbon layer, generate ammonia and nitrogen dioxide gas to further dilute oxygen and combustible gas, the modifier is hydroxyethyl methacrylate and epichlorohydrin to react, so that the hydroxyl group on hydroxyethyl methacrylate reacts with the epoxy group on epichlorohydrin, and then closes the ring under alkaline conditions to form a new epoxy group, to obtain intermediate 4, intermediate 4 is reacted with 1,3-bis(aminopropyl)tetramethyldisiloxane, so that the epoxy group on intermediate 4 reacts with the amino group on 1,3-bis(aminopropyl)tetramethyldisiloxane to form a new hydroxyl group, to obtain intermediate 5, intermediate 5 is reacted with diphenyl chlorophosphate under the action of triethylamine, so that the hydroxyl group on intermediate 5 and the PC on diphenyl chlorophosphate react, l bond reaction to obtain a modifier, the modifier, methyl methacrylate and butyl methacrylate are subjected to free radical polymerization under light to make the polymer molecules into a dense grid shape, which can form a dense carbonized layer on the floor surface when burned, and is used in conjunction with the flame retardant enhancer in the base layer to simultaneously perform flame retardancy on the inside and outside of the template, greatly improving the flame retardant efficiency. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A fireproof biomass molded floor, comprising a sound-proof foam layer, a base layer, a middle material layer, a printed film layer, a wear-resistant layer and a UV coating layer arranged in sequence from bottom to top;

[0030] The silent foam layer and the base layer are equipped with lock buckles for splicing between floors, and the silent foam layer and the base layer are coated with adhesive, which is 194CPVC glue;

[0031] The base layer includes the following raw materials in parts by weight: 90 parts of PVC resin powder type 5, 90 parts of PVC resin powder type 7, 50 parts of wood fiber, 200 parts of calcium carbonate, 100 parts of recycled materials, 10 parts of flame retardant enhancer, 10 parts of stabilizer, 20 parts of foaming regulator, 1 part of internal lubricant, 1 part of external lubricant, 0.5 parts of white foaming agent, 0.5 parts of yellow foaming agent, 3 parts of 2-hydroxyethyl acrylate and 1 part of oxidized wax;

[0032] The stabilizer is calcium zinc stabilizer RUP-108, the foaming regulator is ZB-530, the internal lubricant is G16, the external lubricant is HD-70S, the white foaming agent is MS-107, and the yellow foaming agent is D60;

[0033] The middle material layer is made of the following raw materials in parts by weight: 100 parts of PVC resin powder type 5, 400 parts of calcium carbonate, 35 parts of dioctyl terephthalate and 3 parts of stabilizer;

[0034] The stabilizer is the same as the stabilizer for the base layer;

[0035] The wear-resistant layer is made of surface paper with aluminum oxide added and impregnated with melamine resin;

[0036] The UV coating layer is made of the following raw materials in parts by weight: 20 parts of a modifier, 40 parts of methyl methacrylate, 10 parts of butyl methacrylate, 5 parts of a photoinitiator, 0.3 parts of a leveling agent and 20 parts of toluene.

[0037] The photoinitiator is 1173 and the leveling agent is BYK-320.

[0038] The flame retardant reinforcing agent is prepared by the following steps:

[0039] Step A1: 4-formylphenylboronic acid, 2-aminobenzimidazole and ethanol were mixed evenly, reacted at a speed of 120 r / min and a temperature of 75° C. for 20 h, then cooled to 20 h, DOPO was added, and the reaction was continued for 10 h to obtain intermediate 1;

[0040] Step A2: Trimethylolpropane monoallyl ether, intermediate 1 and toluene are mixed uniformly, nitrogen is introduced for protection, and reflux reaction is carried out at a speed of 60 r / min and a temperature of 115° C. for 3 h to obtain intermediate 2; intermediate 2, tetramethyltetrahydrocyclotetrasiloxane and DMF are mixed uniformly, and chloroplatinic acid is added at a speed of 150 r / min and a temperature of 50° C. to react for 10 h to obtain intermediate 3;

[0041] Step A3: The intermediate 3, zinc nitrate hexahydrate and DMF are mixed, stirred for 1 hour at a speed of 300 r / min and a temperature of 25°C, aged for 20 hours, filtered to remove the filtrate, the substrate is dispersed in deionized water, magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride are added, reacted for 10 hours at a speed of 120 r / min and a temperature of 110°C, filtered and washed to neutrality to obtain a flame retardant enhancer.

[0042] The molar ratio of 4-formylphenylboronic acid, 2-aminobenzimidazole and DOPO in step A1 is 1:1:1.

[0043] The amount ratio of trimethylolpropane monoallyl ether and intermediate 1 described in step A2 is 1:1, the molar ratio of intermediate 2 and tetramethyltetrahydrocyclotetrasiloxane is 4:1, and the amount of chloroplatinic acid used is 1‰ of the mass of tetramethyltetrahydrocyclotetrasiloxane.

[0044] The molar ratio of the intermediate 3, zinc nitrate hexahydrate, magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride described in step A3 is 6:18:15:5:60:20.

[0045] The modifier is prepared by the following steps:

[0046] Step B1: hydroxyethyl methacrylate, aluminum chloride and DMF were mixed evenly, and epichlorohydrin was added under stirring at a speed of 120 r / min and a temperature of 80° C. After reacting for 1 hour, sodium hydroxide solution was added and the reaction was continued for 2 hours to obtain intermediate 4;

[0047] Step B2: Mix the intermediate 4, 1,3-bis(aminopropyl)tetramethyldisiloxane and DMF evenly, and react for 6 hours at a speed of 150 r / min, a temperature of 30°C and a pH of 9 to obtain the intermediate 5. Mix the intermediate 5, triethylamine and DMF evenly, add diphenyl chlorophosphate at a speed of 60 r / min and a temperature of 60°C, and react for 20 hours to obtain the modifier.

[0048] The hydroxyethyl methacrylate, aluminum chloride, epichlorohydrin and sodium hydroxide solution described in step B1 are 1 mol:8.5 mmol:1 mol:160 mL, and the mass fraction of the sodium hydroxide solution is 35%.

[0049] The molar ratio of intermediate 4 and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B2 is 4:1, and the molar ratio of intermediate 5, triethylamine and diphenyl chlorophosphate is 1:4:4.

[0050] The production process of the fireproof biomass molded floor specifically includes the following steps:

[0051] The wear-resistant layer, printed film layer, middle material layer and base layer are overlapped and molded in sequence from top to bottom, lock buckles are installed between the base layer and the silent foam layer and adhesive is applied to bond them, a UV coating layer is coated on the surface of the wear-resistant layer and ultraviolet curing is performed to obtain a fire-resistant biomass molded floor.

[0052] Example 2

[0053] A fireproof biomass molded floor, comprising a sound-proof foam layer, a base layer, a middle material layer, a printed film layer, a wear-resistant layer and a UV coating layer arranged in sequence from bottom to top;

[0054] The silent foam layer and the base layer are equipped with lock buckles for splicing between floors, and the silent foam layer and the base layer are coated with adhesive, which is 714CPVC glue;

[0055] The base layer comprises the following raw materials in parts by weight: 90 parts of PVC resin powder type 5, 90 parts of PVC resin powder type 7, 55 parts of wood fiber, 210 parts of calcium carbonate, 120 parts of recycled materials, 13 parts of flame retardant enhancer, 11 parts of stabilizer, 20 parts of foaming regulator, 2 parts of internal lubricant, 1.28 parts of external lubricant, 0.84 parts of white foaming agent, 0.84 parts of yellow foaming agent, 3.6 parts of 2-hydroxyethyl acrylate and 1.2 parts of oxidized wax;

[0056] The stabilizer is calcium zinc stabilizer RUP-108L, the foaming regulator is ZB-750, the internal lubricant is G60, the external lubricant is G70L, the white foaming agent is MS-109, and the yellow foaming agent is DF801;

[0057] The middle material layer is made of the following raw materials in parts by weight: 100 parts of PVC resin powder type 5, 450 parts of calcium carbonate, 39 parts of dioctyl terephthalate and 4 parts of stabilizer;

[0058] The stabilizer is the same as the stabilizer for the base layer;

[0059] The wear-resistant layer is made of surface paper with aluminum oxide added and impregnated with melamine resin;

[0060] The UV coating layer is made of the following raw materials in parts by weight: 25 parts of a modifier, 45 parts of methyl methacrylate, 13 parts of butyl methacrylate, 6 parts of a photoinitiator, 0.4 parts of a leveling agent and 25 parts of toluene.

[0061] The photoinitiator is 184 and the leveling agent is BYK-331.

[0062] The flame retardant reinforcing agent is prepared by the following steps:

[0063] Step A1: 4-formylphenylboronic acid, 2-aminobenzimidazole and ethanol were mixed evenly, reacted at a speed of 120 r / min and a temperature of 78° C. for 25 h, then cooled to 20 h, DOPO was added, and the reaction was continued for 13 h to obtain intermediate 1;

[0064] Step A2: Trimethylolpropane monoallyl ether, intermediate 1 and toluene are mixed uniformly, nitrogen is introduced for protection, and reflux reaction is carried out at a speed of 60 r / min and a temperature of 120° C. for 4 hours to obtain intermediate 2; intermediate 2, tetramethyltetrahydrocyclotetrasiloxane and DMF are mixed uniformly, and chloroplatinic acid is added at a speed of 200 r / min and a temperature of 55° C. to react for 13 hours to obtain intermediate 3;

[0065] Step A3: Mix the intermediate 3, zinc nitrate hexahydrate and DMF, stir for 1.3 hours at a speed of 300 r / min and a temperature of 28°C, age for 25 hours, filter and remove the filtrate, disperse the substrate in deionized water, add magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride, react for 15 hours at a speed of 120 r / min and a temperature of 113°C, filter and wash to neutrality to obtain a flame retardant enhancer.

[0066] The molar ratio of 4-formylphenylboronic acid, 2-aminobenzimidazole and DOPO in step A1 is 1:1:1.

[0067] The amount ratio of trimethylolpropane monoallyl ether and intermediate 1 described in step A2 is 1:1, the molar ratio of intermediate 2 and tetramethyltetrahydrocyclotetrasiloxane is 4:1, and the amount of chloroplatinic acid used is 1‰ of the mass of tetramethyltetrahydrocyclotetrasiloxane.

[0068] The molar ratio of the intermediate 3, zinc nitrate hexahydrate, magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride described in step A3 is 6:18:15:5:60:20.

[0069] The modifier is prepared by the following steps:

[0070] Step B1: hydroxyethyl methacrylate, aluminum chloride and DMF were mixed evenly, and epichlorohydrin was added under stirring at a speed of 120 r / min and a temperature of 83° C. After reacting for 1-1.5 h, sodium hydroxide solution was added and the reaction was continued for 3 h to obtain intermediate 4;

[0071] Step B2: Mix the intermediate 4, 1,3-bis(aminopropyl)tetramethyldisiloxane and DMF evenly, and react for 7 hours at a speed of 150 r / min, a temperature of 35°C and a pH value of 10 to obtain the intermediate 5. Mix the intermediate 5, triethylamine and DMF evenly, add diphenyl chlorophosphate at a speed of 60 r / min and a temperature of 65°C, and react for 25 hours to obtain the modifier.

[0072] The hydroxyethyl methacrylate, aluminum chloride, epichlorohydrin and sodium hydroxide solution described in step B1 are 1 mol:8.5 mmol:1 mol:160 mL, and the mass fraction of the sodium hydroxide solution is 35%.

[0073] The molar ratio of intermediate 4 and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B2 is 4:1, and the molar ratio of intermediate 5, triethylamine and diphenyl chlorophosphate is 1:4:4.

[0074] The production process of the fireproof biomass molded floor specifically includes the following steps:

[0075] The wear-resistant layer, printed film layer, middle material layer and base layer are overlapped and molded in sequence from top to bottom, lock buckles are installed between the base layer and the silent foam layer and adhesive is applied to bond them, a UV coating layer is coated on the surface of the wear-resistant layer and ultraviolet curing is performed to obtain a fire-resistant biomass molded floor.

[0076] Example 3

[0077] A fireproof biomass molded floor, comprising a sound-proof foam layer, a base layer, a middle material layer, a printed film layer, a wear-resistant layer and a UV coating layer arranged in sequence from bottom to top;

[0078] The mute foam layer and the base layer are equipped with locks for splicing between floors, and the mute foam layer and the base layer are coated with adhesive, and the adhesive is HY-T160;

[0079] The base layer comprises the following raw materials in parts by weight: 100 parts of PVC resin powder type 5, 100 parts of PVC resin powder type 7, 60 parts of wood fiber, 220 parts of calcium carbonate, 150 parts of recycled materials, 15 parts of flame retardant enhancer, 15 parts of stabilizer, 25 parts of foaming regulator, 3 parts of internal lubricant, 3 parts of external lubricant, 1 part of white foaming agent, 0.5-1 part of yellow foaming agent, 5 parts of 2-hydroxyethyl acrylate and 1.5 parts of oxidized wax;

[0080] The stabilizer is calcium zinc stabilizer RUP-151, the foaming regulator is P-530A, the internal lubricant is LG10, the external lubricant is G74, the white foaming agent is MS-110, and the yellow foaming agent is BTC-108;

[0081] The middle material layer is made of the following raw materials in parts by weight: 120 parts of PVC resin powder type 5, 500 parts of calcium carbonate, 45 parts of dioctyl terephthalate and 5 parts of stabilizer;

[0082] The stabilizer is the same as the stabilizer for the base layer;

[0083] The wear-resistant layer is made of surface paper with aluminum oxide added and impregnated with melamine resin;

[0084] The UV coating layer is made of the following raw materials in parts by weight: 30 parts of a modifier, 50 parts of methyl methacrylate, 15 parts of butyl methacrylate, 8 parts of a photoinitiator, 0.5 parts of a leveling agent and 30 parts of toluene.

[0085] The photoinitiator is TPO and the leveling agent is BYK-341.

[0086] The flame retardant reinforcing agent is prepared by the following steps:

[0087] Step A1: 4-formylphenylboronic acid, 2-aminobenzimidazole and ethanol were mixed evenly, reacted at a speed of 150 r / min and a temperature of 78° C. for 25 h, then cooled to 25 h, DOPO was added, and the reaction was continued for 15 h to obtain intermediate 1;

[0088] Step A2: Trimethylolpropane monoallyl ether, intermediate 1 and toluene are mixed uniformly, nitrogen is introduced for protection, and reflux reaction is carried out at a speed of 80 r / min and a temperature of 120° C. for 5 h to obtain intermediate 2; intermediate 2, tetramethyltetrahydrocyclotetrasiloxane and DMF are mixed uniformly, and chloroplatinic acid is added at a speed of 200 r / min and a temperature of 60° C. to react for 15 h to obtain intermediate 3;

[0089] Step A3: The intermediate 3, zinc nitrate hexahydrate and DMF are mixed, stirred for 1.5 hours at a speed of 500 r / min and a temperature of 30°C, aged for 25 hours, filtered to remove the filtrate, the substrate is dispersed in deionized water, magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride are added, reacted for 15 hours at a speed of 150 r / min and a temperature of 115°C, filtered and washed to neutrality to obtain a flame retardant enhancer.

[0090] The molar ratio of 4-formylphenylboronic acid, 2-aminobenzimidazole and DOPO in step A1 is 1:1:1.

[0091] The amount ratio of trimethylolpropane monoallyl ether and intermediate 1 described in step A2 is 1:1, the molar ratio of intermediate 2 and tetramethyltetrahydrocyclotetrasiloxane is 4:1, and the amount of chloroplatinic acid used is 1‰ of the mass of tetramethyltetrahydrocyclotetrasiloxane.

[0092] The molar ratio of the intermediate 3, zinc nitrate hexahydrate, magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride described in step A3 is 6:18:15:5:60:20.

[0093] The modifier is prepared by the following steps:

[0094] Step B1: hydroxyethyl methacrylate, aluminum chloride and DMF were mixed evenly, and epichlorohydrin was added under stirring at a speed of 150 r / min and a temperature of 85° C. After reacting for 1.5 h, sodium hydroxide solution was added and the reaction was continued for 3 h to obtain intermediate 4;

[0095] Step B2: Mix intermediate 4, 1,3-bis(aminopropyl)tetramethyldisiloxane and DMF evenly, and react for 8 hours at a speed of 200 r / min, a temperature of 40°C and a pH value of 10 to obtain intermediate 5. Mix intermediate 5, triethylamine and DMF evenly, add diphenyl chlorophosphate at a speed of 80 r / min and a temperature of 65°C, and react for 25 hours to obtain a modifier.

[0096] The hydroxyethyl methacrylate, aluminum chloride, epichlorohydrin and sodium hydroxide solution described in step B1 are 1 mol:8.5 mmol:1 mol:160 mL, and the mass fraction of the sodium hydroxide solution is 35%.

[0097] The molar ratio of intermediate 4 and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B2 is 4:1, and the molar ratio of intermediate 5, triethylamine and diphenyl chlorophosphate is 1:4:4.

[0098] The production process of the fireproof biomass molded floor specifically includes the following steps:

[0099] The wear-resistant layer, printed film layer, middle material layer and base layer are overlapped and molded in sequence from top to bottom, lock buckles are installed between the base layer and the silent foam layer and adhesive is applied to bond them, a UV coating layer is coated on the surface of the wear-resistant layer and ultraviolet curing is performed to obtain a fire-resistant biomass molded floor.

[0100] Comparative Example 1

[0101] Compared with Example 1, this comparative example uses intermediate 3, zinc nitrate hexahydrate and DMF to mix, stirs for 1.5 hours at a speed of 500 r / min and a temperature of 30°C, ages for 25 hours, and removes the filtrate by filtering. The obtained substrate replaces the flame retardant enhancer, and the remaining steps are the same.

[0102] Comparative Example 2

[0103] Compared with Example 1, this comparative example uses magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride, and reacts for 15 hours at a speed of 150 r / min and a temperature of 115° C., then filters and washes to neutrality. The obtained product replaces the flame retardant enhancer, and the remaining steps are the same.

[0104] Comparative Example 3

[0105] Compared with Example 1, this comparative example uses magnesium hydroxide instead of the flame retardant reinforcing agent, and the other steps are the same.

[0106] Comparative Example 4

[0107] Compared with Example 1, no modifier was added in this comparative example, and the remaining steps were the same.

[0108] Comparative Example 5

[0109] Compared with Example 1, this comparative example uses hydroxyethyl methacrylate to replace intermediate 5, and the remaining steps are the same.

[0110] The boards without the sound-proof foam layer prepared in Examples 1-3 and 1-5 were made into samples of 130 mm × 7.5 mm × 12 mm, and the limit oxygen index was detected according to the standard of ASTM D2863. According to the standard of GB / T2408-2008, samples of 130 mm × 15 mm × 12 mm were made to detect the vertical burning level. The test results are shown in the following table.

[0111]

[0112] It can be seen from the above table that this application has a very good flame retardant effect.

[0113] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A fireproof biomass molded floor, characterized by: It includes a silent foam layer, a base layer, a middle material layer, a printing film layer, a wear-resistant layer and a UV coating layer arranged in sequence from bottom to top; The silent foam layer and the base layer are provided with lock buckles for splicing the floors, and the silent foam layer and the base layer are coated with adhesive; The base layer comprises the following raw materials in parts by weight: 90-100 parts of PVC resin powder type 5, 90-100 parts of PVC resin powder type 7, 50-60 parts of wood fiber, 200-220 parts of calcium carbonate, 100-150 parts of recycled materials, 10-15 parts of flame retardant enhancer, 10-15 parts of stabilizer, 20-25 parts of foaming regulator, 1-3 parts of internal lubricant, 1-3 parts of external lubricant, 0.5-1 parts of white foaming agent, 0.5-1 parts of yellow foaming agent, 3-5 parts of 2-hydroxyethyl acrylate and 1-1.5 parts of oxidized wax; The middle material layer is made of the following raw materials in parts by weight: 100-120 parts of PVC resin powder type 5, 400-500 parts of calcium carbonate, 35-45 parts of dioctyl terephthalate and 3-5 parts of stabilizer; The UV coating layer is made of the following raw materials in parts by weight: 20-30 parts of a modifier, 40-50 parts of methyl methacrylate, 10-15 parts of butyl methacrylate, 5-8 parts of a photoinitiator, 0.3-0.5 parts of a leveling agent and 20-30 parts of toluene; The flame retardant reinforcing agent is prepared by the following steps: Step A1: After 4-formylphenylboronic acid, 2-aminobenzimidazole and ethanol are mixed for reaction, DOPO is added and the reaction is continued to obtain intermediate 1; Step A2: trimethylolpropane monoallyl ether, intermediate 1 and toluene are mixed and refluxed to react to obtain intermediate 2; intermediate 2, tetramethyltetrahydrocyclotetrasiloxane and DMF are mixed and stirred, and chloroplatinic acid is added to react to obtain intermediate 3; Step A3: The intermediate 3, zinc nitrate hexahydrate and DMF are mixed and stirred, and then aged, and the filtrate is filtered to remove the filtrate, the substrate is dispersed in deionized water, magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride are added, and after reacting, the mixture is filtered and washed to neutrality to obtain a flame retardant enhancer; The modifier is prepared by the following steps: Step B1: hydroxyethyl methacrylate, aluminum chloride and DMF are mixed and stirred, and epichlorohydrin is added. After the reaction, sodium hydroxide solution is added and the reaction is continued to obtain intermediate 4; Step B2: The intermediate 4, 1,3-bis(aminopropyl)tetramethyldisiloxane and DMF are mixed and reacted to obtain the intermediate 5. The intermediate 5, triethylamine and DMF are evenly mixed, and diphenyl chlorophosphate is added to react to obtain the modifier.

2. The fireproof biomass molded floor according to claim 1, characterized in that: The molar ratio of 4-formylphenylboronic acid, 2-aminobenzimidazole and DOPO in step A1 is 1:1:

1.

3. The fireproof biomass molded floor according to claim 1, characterized in that: The amount ratio of trimethylolpropane monoallyl ether and intermediate 1 described in step A2 is 1:1, and the molar ratio of intermediate 2 and tetramethyltetrahydrocyclotetrasiloxane is 4:

1.

4. The fireproof biomass molded floor according to claim 1, characterized in that: The molar ratio of the intermediate 3, zinc nitrate hexahydrate, magnesium chloride hexahydrate, aluminum chloride nonahydrate, sodium hydroxide and ammonium fluoride described in step A3 is 6:18:15:5:60:

20.

5. The fireproof biomass molded floor according to claim 1, characterized in that: The hydroxyethyl methacrylate, aluminum chloride, epichlorohydrin and sodium hydroxide solution described in step B1 are 1 mol: 8.5 mmol: 1 mol: 160 mL.

6. The fireproof biomass molded floor according to claim 1, characterized in that: The molar ratio of intermediate 4 and 1,3-bis(aminopropyl)tetramethyldisiloxane described in step B2 is 4:1, and the molar ratio of intermediate 5, triethylamine and diphenyl chlorophosphate is 1:4:

4.

7. The production process of a fireproof biomass molded floor according to claim 1, characterized in that: The specific steps include: The wear-resistant layer, printed film layer, middle material layer and base layer are overlapped and molded in sequence from top to bottom, lock buckles are installed between the base layer and the silent foam layer and adhesive is applied to bond them, a UV coating layer is coated on the surface of the wear-resistant layer and ultraviolet curing is performed to obtain a fire-resistant biomass molded floor.

Citation Information

Patent Citations

  • Fireproof and heat-insulating paint, preparation method and application thereof

    CN110862748A

  • Ultra-high-gloss and ultra-wear-resistant CSPC biomass composite floor

    CN115573537A

  • Fireproof biomass molded floor and production process thereof

    CN118241835A

  • Halogen-free watertight floor sheet for vehicle

    JP2008045064A

  • Flooring structure

    JP3174309U